Metabolite profiling and bioactivity guided fractionation of Lactobacillaceae and rice bran postbiotics for antimicrobial-resistant Salmonella Typhimurium growth suppression - Nealon, Nora Jean; Worcester, Colette R.; Boyer, Shea M.; Haberecht, Hannah B.; Ryan, Elizabeth P. (Frontiers in Microbiology, 2024)
Probiotic-fermented supplements (postbiotics) are becoming increasingly explored for their activity against antibiotic resistant enteropathogens. Prebiotics are often incorporated into postbiotics to enhance their efficacy, but due to strain differences in probiotic activity, postbiotic antimicrobial effects are poorly understood. To improve postbiotic antimicrobial efficacy, we investigated and compared metabolite profiles of postbiotics prepared with three lactic acid bacteria strains (L. fermentum, L. paracasei, L. rhamnosus) cultured with and without rice bran, a globally abundant, rich source of prebiotics. At their minimum inhibitory dose, L. fermentum and L. paracasei postbiotics + rice bran suppressed S. Typhimurium growth 42-55% more versus their respective probiotic-alone postbiotics. The global, non-targeted metabolome of these postbiotics identified 86 metabolites increased in L. fermentum and L. paracasei rice bran postbiotics, including 46 amino acid, 15 lipid, and 11 phytochemical metabolites. To identify key metabolite contributors to postbiotic antimicrobial activity, bioactivity-guided fractionation was applied to L. fermentum and L. paracasei rice bran-fermented postbiotics. Fractionation resulted in four L. fermentum and seven L. paracasei fractions capable of suppressing S. Typhimurium growth more effectively versus the negative control. These fractions were enriched in 15 metabolites that were significantly increased in the global metabolome of postbiotics prepared with rice bran versus postbiotic alone. These metabolites included imidazole propionate (enriched in L. fermentum + rice bran, 1.61-fold increase; L. paracasei + rice bran 1.28-fold increase), dihydroferulate (L. fermentum + rice bran, 5.18-fold increase), and linoleate (L. fermentum + rice bran, 1.82-fold increase; L. paracasei + rice bran, 3.19-fold increase), suggesting they may be key metabolite drivers of S. Typhimurium growth suppression. Here we show distinct mechanisms by which postbiotics prepared with lactic acid bacteria and rice bran produce metabolites with antimicrobial activity capable of suppressing S. Typhimurium growth. Probiotic strain differences contributing to postbiotic antimicrobial activity merit attention as adjunctive treatments against pathogens.